2015
DOI: 10.1112/plms/pdv051
|View full text |Cite
|
Sign up to set email alerts
|

The degeneration of convex ℝℙ2structures on surfaces

Abstract: Let M be a compact surface of negative Euler characteristic and let C(M ) be the deformation space of convex real projective structures on M . For every choice of pants decomposition for M , there is a well known parameterization of C(M ) known as the Goldman parameterization. In this paper, we study how some geometric properties of the real projective structure on M degenerate as we deform it so that the internal parameters of the Goldman parameterization leave every compact set while the boundary invariants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…However, it is clear that the intersection number is not symmetric on the Hitchin component. For example, one may use the work of Zhang [94,95] to exhibit for all K > 1 and…”
Section: Corollary 510 Entropy Varies Analytically Over H D (S) Andmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is clear that the intersection number is not symmetric on the Hitchin component. For example, one may use the work of Zhang [94,95] to exhibit for all K > 1 and…”
Section: Corollary 510 Entropy Varies Analytically Over H D (S) Andmentioning
confidence: 99%
“…(2) Tengren Zhang [94,95] showed that, for all d, there exist large families of sequences of Hitchin representations with entropy converging to 0. Nie [64] had earlier constructed specific examples when d = 3.…”
Section: Rigidity Theorems For Hitchin Representationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance compactifications of spaces of representations of Γ have been introduced and studied in [Par12,Ale08,Le12]. In the context of Hitchin representations, asymptotic properties of diverging sequences are studied in [Zha13,Zha14,CL14,Lof15,Par15,KNPS15,MSWW14].…”
Section: Introductionmentioning
confidence: 99%